Identification of serum metabolite biomarkers in premature infants with bronchopulmonary dysplasia: protocol for a multicentre prospective observational cohort study - Ping Zhou; Jun Chen; Ying Liu; Cheng Chen; Xin Guo; Zhangbin Yu; Jiebo Liu; Yanping Guo; Dan Dan Rao; Shengnan He; Xudong Yan; Wanxiang He; et al. (BMJ Open)
Introduction Bronchopulmonary dysplasia (BPD) is one of the most common and significant complications of preterm birth. It ultimately leads to a decrease in the quality of life for preterm infants and impacts their long-term health. Early prediction and timely intervention are crucial to halting the development of BPD. This study aims to identify the biomarkers that can predict the early occurrence and development of BPD by screening serum metabolites in preterm infants. This will provide strong support for the early prediction of BPD and targeted interventions in future research.Methods and analysis This is a prospective, multicentre, open-label, observational cohort study spanning 3 years. It will be conducted in six major neonatal intensive care units in Shenzhen, China, involving preterm infants born at gestational ages <32 weeks. Demographic data and treatment information will be collected prospectively. Serum samples will be collected at five distinct time points: within 24 hours after birth, at 1 week, 2 weeks, 28 days and at 36 weeks postmenstrual age. These samples will undergo analysis using liquid chromatography-tandem mass spectrometry for untargeted metabolomics studies. Participants will be categorised into BPD and non-BPD groups based on their final diagnosis, and metabolite differences between these groups will be analysed. The study aims to enrol 1500 preterm infants with gestational ages <32 weeks over 3 years. A three-step analysis strategy—discovery, validation and clinical testing—will be used to identify and validate the clinical utility of novel biomarkers. Additionally, a nested case-control study will be conducted, matching participants 1:1 with a control group sharing similar BPD risk factors.Ethics and dissemination Our protocol has been approved by the Medical Ethics Committees of all participating hospitals, including Peking University Shenzhen Hospital, Shenzhen People’s Hospital, Shenzhen Baoan Women’s and Children’s Hospital, Longgang District Maternity and Child Healthcare Hospital, Nanshan Maternity and Child Healthcare Hospital and Shenzhen Luohu People’s Hospital. We will disseminate our study results through academic conferences and peer-reviewed public journals.Trial registration number ChiCTR2400081615.